1989
DOI: 10.1007/bf02556465
|View full text |Cite
|
Sign up to set email alerts
|

Increased circulating levels of γ-carboxyglutamic acid-containing protein and decreased bone mass in children on anticonvulsant therapy

Abstract: In order to investigate the pathophysiology of anticonvulsant-induced osteopenia, circulating levels of bone gamma-carboxyglutamic acid-containing protein (Bone Gla Protein: BGP) and urinary excretion of BGP were measured in 16 children on chronic anticonvulsant therapy and in 12 control children. Using microdensitometry analysis, osteopenia was found in 25% of the anticonvulsant therapy group, but it was not observed in the control group. Serum BGP and A1-P levels were significantly increased in the anticonvu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…However, in previous works of this nature, other authors have found an increase in these bone formation markers [13, 14, 21, 23, 55,61,62,63] and in vitro, in human osteoblast cultures, having demonstrated an osteogenic effect of the DPH that brings with it an increase in the number of osteoblasts, an increase in the synthesis of collagen, and an increase in the production of BGP [10,11,12,13, 15, 23, 61]. With respect to the BGP, it seems that the treatment of an altered or different BGP, not γ-carboxylated, passes directly to the serum, not to the bone matrix which would nevertheless be deficient in osteocalcin [15].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, in previous works of this nature, other authors have found an increase in these bone formation markers [13, 14, 21, 23, 55,61,62,63] and in vitro, in human osteoblast cultures, having demonstrated an osteogenic effect of the DPH that brings with it an increase in the number of osteoblasts, an increase in the synthesis of collagen, and an increase in the production of BGP [10,11,12,13, 15, 23, 61]. With respect to the BGP, it seems that the treatment of an altered or different BGP, not γ-carboxylated, passes directly to the serum, not to the bone matrix which would nevertheless be deficient in osteocalcin [15].…”
Section: Discussionmentioning
confidence: 89%
“…In the degree of mineralization, we have noted two forms in our patient groups: one with low mineralization (low bone turnover) or osteomalacia [4,59,60,61,62] and the other with high mineralization (high bone turnover) typical of the hyperparathyroid states characterized by a depleting cortical bone and conservation of the trabecular bone [26]. Cases with normal mineralization have also been described.…”
Section: Discussionmentioning
confidence: 92%
“…Urinary pyridinolines may be increased 3-fold whereas the increases in markers of bone formation and the serum marker of bone resorption, CTX-MMP, are smaller. The increases in men (50±100%) are greater than in women (10±30%) and appear to be independent of the type of anticonvulsant drug [110,111]. Thiazide diuretics decrease bone turnover.…”
Section: Drugsmentioning
confidence: 91%
“…Patients under anticonvulsant therapy (phenytoin and phénobarbital) were selected for this trial because this association of drugs induces more marked effects on calciotropic hormones [11], PTH values did not change in our patients when compared to controls and showed a negative correlation with CaC values, which was a physio logical condition [ 12], CT did not change either, and, as is the case under physiological conditions, there was a posi tive correlation with CaC [13], As in our case, although with a younger population group, Takesita et al [14] did neither observe PTH nor CT changes. Other authors, such as Weinstein et al [15], found decreased ionic calcium and increased PTH.…”
Section: Discussionmentioning
confidence: 53%
“…On the other hand, Schmitt et al [ 16] reported that 27% of the patients under anticonvulsant treatment had hypocalcemia, and Hahn et al [17] also pointed out that calcemia levels were decreased, and PTH levels were increased. Mosekilde et al [ 18] just like Take sita et al [14] and us, also did not find PTH changes; and calcemia changes were neither observed by Murchinson et al [19] nor by Takesita et al [14], We consider that such discrepancies depend on the techniques used. We evaluated CaC while other authors [ 15] reported changes in ionic calcium.…”
Section: Discussionmentioning
confidence: 58%